PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING DISERTAI KUIS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPS SMAN 1 LEMBAH GUMANTI - Safriani, Yuri; Aima, Zulfitri; Sovia, Anny (Pendidikan Matematika, 2013)
This research was conducted based of the fact that comprehension of mathematical concept for students was not satisfied yet. It could be seen from their low learning achievement in Math. This research was aimed at revealing the development of studentsâ mathematics concept and whether the use of Guided Note Taking active learning strategy accompanied with Quiz could improve the second year comprehension of mathematical concept for studentsâ better than that of conventional learning in class XI Sosial Science classes of Â SMAN 1 Lembah Gumanti. This was an Â experimental research. The population of the research was the students in class XI of Sosial Science Classes of SMAN 1 Lembah Gumanti registered in Academic Year 2013/2014. From the populaion, class XI IPS.1 was chosen as the experimental class and class XI IPS.3 as the control class. The instruments of the research was a quiz and a post-test in the from of essay whose realibility was r11=0,948. The data gotten then was analyzed by using normality test, homogeneity test and t-test. The result of hypothesis test showed that p-vaue was 0.010 (Î±=0.05) indicating that H0 was rejected. In conclusion, the comprehension of mathematical concept for active learning strategyâs students type Guided Note Takin with Quiz were better than implemented conventional learningâs students for grade XI of Sosial Science Classes of SMAN 1 Lembah Gumanti.